Women Empowerment in Indonesia: Community Learning Activity Center Programs - Dadi Dadi (AL-ISHLAH: Jurnal Pendidikan, 2021)
One of the factors that support the progress of a nation is the participation of women in community development. Educated women are crucial aspects in improving the quality of human resources. The government together with the community, have responsibilities and play an essential role in facilitating educational activities for women. Community Learning Activity Center (PKBM), as an institution established and managed by the society to increase knowledge, skills, expertise and talents, is responsible for preparing community members to be more independent in meeting their needs, especially in the program for marginalized women empowerment. Among the programs, Women's Life Skills Education Program (PKHP) presents as an alternative solution to provide facilities for women to grow. Many researchers documented the activities in this program and published them in Community Service journals or scientific journals. Therefore, the current study would shed light on the efforts they made by implementing a literature study. By analysing using narrative synthesis studies, the findings reported on diverse activities that were created to develop women’s life skills by utilizing the local natural resource potential as well as the methods of delivery and prospected outcomes. This study also provides some practical implications and future recommendations.